Novel mutations of COL4A3, COL4A4, and COL4A5 genes in Chinese patients with Alport Syndrome using next generation sequence technique. Issue 6 (9th April 2019) - Zhao, Xuechao; Chen, Chen; Wei, Yanfu; Zhao, Ganye; Liu, Lina; Wang, Conghui; Zhang, Junjun; Kong, Xiangdong
Abstract: Background: Alport syndrome (AS) is an inherited progressive renal disease caused by mutations in COL4A3, COL4A4, and COL4A5 genes. The large sizes of these genes and the absence of mutation hot spots have complicated mutational analysis by routine PCR‐based approaches. In recent years, the development of next‐generation sequencing (NGS) has made possible the time‐ and cost‐effective and accurate analysis of the three genes in a single step. Methods: Here, we analyze COL4A3, COL4A4, and COL4A5 simultaneously in 29 AS patients using NGS. Candidate mutations were validated by classic Sanger sequencing and Real‐time PCR. Results: Twenty two new mutations and 10 known mutations were detected. Of those novel mutations, 18, 3, and 1 mutations were detected in COL4A5, COL4A4, and COL4A3, respectively. Twenty six patients showed X ‐linked inheritance, one showed autosomal recessive inheritance and two showed digenic inheritance (DI). Conclusion: A comparison of the clinical manifestations caused by different types of mutations in COL4A5 suggested that large fragment mutations are relatively more severe than the other missense mutations and AS by some mutations may show inter‐ and intra‐familial phenotypic variability. It is important to consider these transmission patterns in the clinical evaluation according to the results of genetic testing, especially for DI. Twenty two new mutations can expand the genotypic spectrum of AS. Abstract : Here, we analyze COL4A3, COL4A4, and COL4A5 simultaneously in 29 AS patients using NGS. Twenty two new mutations and 10 known mutations were detected. Of those novel mutations, 18, 3, and 1 mutations were detected in COL4A5, COL4A4, and COL4A3, respectively. Twenty six patients showed X ‐linked inheritance, one showed autosomal recessive inheritance and two showed digenic inheritance.